2004
DOI: 10.1002/ijc.20138
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of evodiamine on the growth of human prostate cancer cell line LNCaP

Abstract: Key words: prostate cancer; evodiamine; cell growth; G2/M arrest; apoptosisProstate cancer is the most commonly diagnosed malignancy in American men over 40 years of age and is the second leading of cancer deaths. 1,2 Recently, prostate cancer has become more and more common in Asia including Taiwan. 3 According to previous studies, widely accepted risk factors for prostate cancer are age, race, ethnicity, dietary habits, androgen production and metabolism. 4 Prostate cancer is characterized by an initial andr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 40 publications
4
66
2
Order By: Relevance
“…That evodiamine down-regulates Cyclin D1 expression may explain the results from earlier reports indicating that this agent induces G 2 /M arrest rather than G 1 /S arrest (4,5). It also may explain the antiproliferative effects of evodiamine through TNF-induced NF-B-mediated down-regulation of Cyclin D1 by evodiamine.…”
Section: Figmentioning
confidence: 72%
See 1 more Smart Citation
“…That evodiamine down-regulates Cyclin D1 expression may explain the results from earlier reports indicating that this agent induces G 2 /M arrest rather than G 1 /S arrest (4,5). It also may explain the antiproliferative effects of evodiamine through TNF-induced NF-B-mediated down-regulation of Cyclin D1 by evodiamine.…”
Section: Figmentioning
confidence: 72%
“…1) has recently been shown to suppress the proliferation of a wide variety of tumor cells, including prostate cancer cells (4), leukemic T-lymphocytes (5), monocytic leukemia cells (6), melanoma cells (6,7), cervical cancer cells (6), and mouse fibrosarcoma cells (6), but it apparently has no toxic effects against normal peripheral blood mononuclear cells (6). 1 The abbreviations used and trivial name are: evodiamine, 8,13,13b14-tetrahydro-14-methlindolo[2Ј3Ј: 3,4]pyrido [2,1-b]quinazolin-5-[7H]-one; NF-B, nuclear factor-B; IB, inhibitory subunit of NF-B; IKK, IB␣ kinase; TNF, tumor necrosis factor; TNFR, TNF receptor; TRADD, TNFR-associated death domain; NIK, NF-B-inducing kinase; IL, interleukin; SEAP, secretory alkaline phosphatase; PMA, phorbol 12-myristate 13-acetate; TUNEL, terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end-labeling; IAP, inhibitor-of-apoptosis protein; XIAP, X chromosome-linked IAP; FLIP, Fas-associated death domain protein-like IL-1␤-converting enzyme-inhibitory protein; COX, cyclooxygenase; MMP, matrix metalloproteinase; TRAF, TNF receptor-associated factor, PBS, phosphate-buffered saline; ICAM, intercellular adhesion molecule; MDR, multidrug resistance protein; NO, nitric oxide; FBS, fetal bovine serum; JNK, c-Jun NH 2 -terminal kinase; MAPK, mitogen-activated protein kinase; PARP, poly(ADP-ribose) polymerase; EMSA, electrophoretic mobility shift assay; GST, glutathione S-transferase; MTT, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide.…”
mentioning
confidence: 99%
“…Currently, evidence indicates that EVO possesses anticancer activities. EVO is reported to hinder tumor development by inhibiting cancer cell proliferation and inducing cell apoptosis in various types of cancer cells, such as lung (14), acute leukemia (15)(16)(17), prostate (18)(19)(20) and cervical (17). Yang et al reported that EVO can upregulate the expression of phosphatase shatterproof 1 (SHP-1) (21), which is the key gene of IL-6-induced signal transducer and activator of transcription signaling 3 (STAT3) signaling leading to the suppression of survival and proliferation in hepatocellular carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products have provided a large number of currently used chemotherapeutics and will continue to be an important component of drug discovery (24,25). Evodiamine, an alkaloidal component extracted from the fruit of Evodiae fructus, has been reported to inhibit various tumor cell proliferations, including monocytic leukemia (26), melanoma (27), prostate cancer (28), and breast cancer cell (29). However, the mechanism underlying its antiproliferative, antimetastatic, and apoptotic activities is poorly defined yet.…”
Section: Introductionmentioning
confidence: 99%